Using digital forensics to improve software reliability. (May 2015) - Bella, Madeleine Bihina; Eloff, Jan
Abstract : IT systems are ubiquitous in today's interconnected society and play a vital role in a number of industries such as banking, telecommunications and aviation. Software, in particular, is embedded in most technical and electronic products, ranging from massive machines such as airplanes to lightweight devices such as mobile phones. Software applications are essential to the proper functioning of these products and their associated service offerings. The use of digital forensics to analyse software failures has been almost exclusively limited to examining problems after they occur. The IT industry would do well to adopt the near-miss management system (NMS) approach used by many other industries. An NMS that combines near-miss analysis and digital forensics can contribute significantly to the improvement of the accuracy of the failure analysis. However, as Madeleine Bihina Bella and Jan Eloff of the University of Pretoria/SAP Innovation Centre, Pretoria explain, there are challenges to implementing an NMS for software.